AB0629 A critical appraisal of the competence of crystal identification by rheumatologists. (23rd January 2014) - Berendsen, D.; Jansen, T. L.; Taylor, W.; Neogi, T.; Fransen, J.; Pascual, E.; Schumacher, H. R.; Dalbeth, N.
Abstract : Background: The gold standard for diagnosing crystal arthritis is aspiration of synovial fluid and subsequent polarized microscopy on the punctured fluid. However, various studies have shown a lack of consistency in results of crystal analysis among different observers. We have proposed to certify dedicated colleagues by confirming skill of crystal identification and to increase our insight in general about expertise with the identification of crystals in synovial fluid. By obtaining these data concerning current microscopical performance, we aim to find areas of crystal recognition which are open for further improvement. Objectives: The primary objective is to confirm the expertise of physicians with the identification of crystals in synovial fluid/tissue. An online test prepared for the Study of Updated Gout criteria: acr/eulaR (SugaR) emphasizes the recognition of monosodium urate (MSU) crystals, plus the identification of a predefined set as non-MSU crystals; this online test also includes identification of other crystals, such as calcium pyrophosphate dihydrate (CPP), cholesterol, oxalate and apatite. Our secondary objective is to find out whether observer factors are related to microscopical performance. Methods: Diagnosticians from different countries, who are working in the rheumatology field and performing microscopic analysis were asked to participate to qualify for entrance to the SugaR Study. The first part of the test included a number of questions concerning personal/professional data. The second part contained 30 slides with images of crystals and other look-a-likes from synovial fluid: crystals shown were 8 MSU, 5 CPP, 4 cholesterol, 2 oxalate and 1 apatite. The test also included slides with potentially confusing look-a-likes. Results: Up to January 1st 2013, 56 persons performed the online test; 46% (n=43) of them identified each one of the 20 crystals correctly. With respect to MSU crystals 77% identified 8 MSU crystals, 91% identified at least 7 out of 8 MSU crystals; 68% of all attendees identified 5 CPP crystals and 91% at least 4 out of 5 CPP crystals. See table . Ability to recognize crystals when they are there (%) Conclusions: Almost half of the attendees performed well at identifying a diversity of crystals: MSU crystals appeared easier to identify than CPP. The objective performance regarding crystal identification can be improved in all. There seems to be no clear relationship between confidence of expertise and actual expertise. Disclosure of Interest: None Declared